2017
DOI: 10.1016/j.jash.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antihypertensive medications and associations with blood pressure among African Americans with hypertension in the Jackson Heart Study

Abstract: The purpose of this study was to test the association between a self-report measure of 24-hour adherence to antihypertensive medication and blood pressure (BP) among African Americans. The primary analysis included 3,558 Jackson Heart Study participants taking antihypertensive medication who had adherence data for at least one study exam. Non-adherence was defined by self-report of not taking one or more prescribed antihypertensive medications, identified during pill bottle review, in the past 24 hours. Non-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Only 43.9% of respondents were certain that their blood pressure is controlled. However, a higher proportion of medication nonadherence was noticed in the uncontrolled blood pressure patients [3,17,18,36]. Poorly controlled or untreated hypertension provokes gradual and irretrievable damage to internal organs, the consequences of which include serious complications or even death.…”
Section: Discussionmentioning
confidence: 99%
“…Only 43.9% of respondents were certain that their blood pressure is controlled. However, a higher proportion of medication nonadherence was noticed in the uncontrolled blood pressure patients [3,17,18,36]. Poorly controlled or untreated hypertension provokes gradual and irretrievable damage to internal organs, the consequences of which include serious complications or even death.…”
Section: Discussionmentioning
confidence: 99%
“…Nonadherence to two aspects of hypertension management, namely prescribed drug regimens and lifestyle recommendations, are the two major challenges that lead to uncontrolled, resistant, and complicated hypertension (heart failure, stroke, and renal failure) [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. There is strong evidence that shows poor adherence to antihypertensive medications is associated with uncontrolled blood pressure among African Americans [ 24 ]. Poor adherence to cardiovascular medications, antihypertensive agents, and statins among older African American adults is also well documented [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that shows poor adherence to antihypertensive medications is associated with uncontrolled blood pressure among African Americans [ 24 ]. Poor adherence to cardiovascular medications, antihypertensive agents, and statins among older African American adults is also well documented [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. For African Americans, poor adherance to antihypertensive medications happens in a context of several other health and medication-related problems.…”
Section: Introductionmentioning
confidence: 99%
“…The current cross‐sectional study was restricted to 1658 JHS participants at Examination 1 who had genetic ancestry information available, had valid BP data from the baseline study visit, taking at least one class of antihypertensive medication, and self‐reported taking all of their antihypertensive medications within the past 24 hours (Figure ). The 24‐hour self‐reported antihypertensive medication adherence measure has been associated with BP control in the JHS . The JHS protocol was approved by the University of Mississippi Medical Center's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…The 24-hour self-reported antihypertensive medication adherence measure has been associated with BP control in the JHS. 13 The JHS protocol was approved by the University of Mississippi Medical Center's Institutional Review Board. The current analysis was approved by the University of Utah's Institutional Review Board.…”
Section: Study Populationmentioning
confidence: 99%